The lives of the popes in the early middle ages - Mann, Horace K. (B. Herder, 1906)
v. 1. The popes under the Lombard rule : St. Gregory I (the Great) to Leo III, 590-795 (2 pts.) -- v. 2-3. The popes during the Carolingian empire : Leo III to Formosus, 795-891 -- v. 4-5. The popes in the days of feudal anarchy : Formosus to Damasus II, 891-1048 -- v. 6-8. The popes of the Gregorian renaissance : St. Leo IX to Honorius II, 1049-1130 -- v. 9-10. The popes at the height of their temporal influence : Innocent II to Blessed Benedict XI, 1130-1305 -- v. 11-12. Innocent III : 1198-1216.